THE APPLICATION OF MOODLE PLATFORM FUNCTIONS TO DEVELOP FOREIGN LANGUAGE LEXICAL COMPETENCY - Stryzhak, Olena; Krapivnyk, Ganna (Journal of Information Technologies in Education (ITE), 2021)
The paper discusses the features of developing foreign language lexical competency while applying the Moodle platform. The development of the foreign language lexical competency is considered as a case study of teaching the Service Marketing course to full-time master’s degree students at Simon Kuznets Kharkiv National University of Economics. The case shows the distance educational course of Service marketing, including the description of its content and structural elements that promote professional competencies. The research proves the need to apply information communication technologies provided by Moodle functionality in developing foreign language lexical competency. The elements of the Moodle information platform that enable to form student’s professional terminology minimum are described. Lexical competency implies not only clarifying etymology and semantics of a language sign but also studying the specifics of its use depending on the content. Therefore, it is offered to educators to apply foreign language materials and develop professional lexical competency. This process is exemplified by the analysis of a television commercial in English and the evaluation of the advert efficiency. The commercial evaluation procedure includes its viewing and identifying the means and methods of its impact on the consumer’s consciousness, which involves learning and analyzing language-related information. It was found out that, in addition to the development of course-related professional competencies, watching and analyzing video materials encourages the development of speaking skills and enriches students’ vocabulary. The benefits and drawbacks of using the Moodle environment for lectures, seminars, students’ individual work, academic performance and knowledge assessment are laid out.